Analisis Perfoma Multi Effect Desalination dengan Metode Overall Equipment Effectiveness Sebelum dan Sesudah Perbaikan di PLTU X - Fauziyyah, Zaida Sahla; Sasono, Teguh; Suprianti, Yanti (SURYA TEKNIKA, 2024)
A multi-effect desalination machine is a device capable of producing fresh water for power plant and domestic water needs. The problem encountered is a decrease in the fresh water produced, which is related to the effectiveness of the multi-effect desalination machine. The method used to measure the machine's effectiveness is the Overall Equipment Effectiveness method. This study aims to calculate the OEE value of the multi-effect desalination machine before and after maintenance and to identify common issues by determining an action plan. The analytical method used to determine failure defense tasks is the Failure Mode and Effect Analysis method. The results showed that the OEE value after maintenance increased compared to the OEE value before maintenance, with the highest OEE value recorded at 91% on August 31 - September 1, 2023. Of the 12 types of damage that occurred, 66.67% affected the performance rate parameter and 33.33% affected the availability rate parameter. The most effective action plan in improving the OEE value after maintenance was the acid cleaning process.